#### Answer

$4x-9y$

#### Work Step by Step

$(2\sqrt x-3\sqrt y)(2\sqrt x+3\sqrt y)$
=$(2\sqrt x)^{2}-(3\sqrt y)^{2}$
=$4(x)-9(y)$
=$4x-9y$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$4x-9y$

$(2\sqrt x-3\sqrt y)(2\sqrt x+3\sqrt y)$
=$(2\sqrt x)^{2}-(3\sqrt y)^{2}$
=$4(x)-9(y)$
=$4x-9y$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.